2005
DOI: 10.4049/jimmunol.174.11.6702
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Long-Term Disappearance of CD4+ T Lymphocyte Responses Specific for Anaplasma Marginale Major Surface Protein-2 (MSP2) in MSP2 Vaccinates following Challenge with Live A. marginale

Abstract: In humans and ruminants infected with Anaplasma, the major surface protein 2 (MSP2) is immunodominant. Numerous CD4+ T cell epitopes in the hypervariable and conserved regions of MSP2 contribute to this immunodominance. Antigenic variation in MSP2 occurs throughout acute and persistent infection, and sequentially emerging variants are thought to be controlled by variant-specific Ab. This study tested the hypothesis that challenge of cattle with Anaplasma marginale expressing MSP2 variants to which the animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
74
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 61 publications
8
74
0
Order By: Relevance
“…However, antigen-specific CD4 ϩ T lymphocytes clearly provide some of the signals for this transition. Consistent with this hypothesis is the observa- tion with A. marginale that, although robust CD4 ϩ T-cell responses specific to both the HVR and conserved domains can be induced by MSP2 immunization (1), these cannot be consistently detected during actual infection (2). Dissecting the mechanism underlying the short-lived antibody responses, both from a structural basis of the HVR and the immunologic basis, will further enhance our understanding of how highly antigenically variant pathogens persist within the infected host.…”
Section: Discussionsupporting
confidence: 54%
“…However, antigen-specific CD4 ϩ T lymphocytes clearly provide some of the signals for this transition. Consistent with this hypothesis is the observa- tion with A. marginale that, although robust CD4 ϩ T-cell responses specific to both the HVR and conserved domains can be induced by MSP2 immunization (1), these cannot be consistently detected during actual infection (2). Dissecting the mechanism underlying the short-lived antibody responses, both from a structural basis of the HVR and the immunologic basis, will further enhance our understanding of how highly antigenically variant pathogens persist within the infected host.…”
Section: Discussionsupporting
confidence: 54%
“…This protection is associated with high IgG2 titers against the immunodominant major surface protein 2 (MSP2) (16) and CD4 ϩ T-lymphocyte proliferative responses to MSP1, MSP2, and MSP3 (16) as well as MSP4 (W. C. Brown, unpublished observations). However, none of these individual proteins has induced protection equivalent to that of the complex outer membrane immunogen (1,16,43,44,48,49,58). This discrepancy in ability to induce protection suggests at least two possible explanations.…”
mentioning
confidence: 99%
“…This experiment confirmed that the infection-induced loss of response was not restricted to the variable MSP2 antigen, but occurred using a different immunization protocol and a conserved protein epitope. Furthermore, for both studies, Anaplasma-specific T cell responses were not detected in peripheral blood lymphocytes from control sham immunized animals following challenge (Abbott et al, 2005; W. C. Brown, unpublished data).…”
mentioning
confidence: 95%
“…These results suggest the sudden loss of MSP2-specific T cell responses in the peripheral blood was not simply due to an increase in regulatory T cells in peripheral blood in response to infection (Abbott et al, 2005). However, the spleens were not evaluated for functional suppressor T cells, which if present, could explain these results, as the spleen is important for removing infected erythrocytes during hemoparasite infections.…”
mentioning
confidence: 95%
See 1 more Smart Citation